Analyse typologique des plans stratégiques des universités québécoises - Larouche, Catherine; Savard, Denis; Héon, Lucie; Moisset, Jean-Joseph (Canadian Journal of Higher Education, 2016)
This research tests the applicability of the typology proposed by Larouche and his collaborators in higher education strategic planning. The typology developed for the assessment of performance, features seven types of concepts defined in terms of seven dimensions. A literature review of 17 strategic plans, conducted according to criteria of clarity and logical consistency, completeness, and usefulness shows that the typology may prove enlightening in the planning process. The results demonstrate that the conceptions are defined clearly enough to be detected in the strategic plans, and these conceptions cover meaningful realities in the documents analyzed, and the typology allows us to understand complex contexts (strategic alignment) that it is sensitive enough to reflect a diversity of situations (characterization of institutions).